Self-collected samples as an additional option for STI testing in low-resource settings: a qualitative study of acceptability among adults in Rakai, Uganda - Ogale, Yasmin Parvizi; Grabowski, Mary Kathryn; Nabakka, Proscovia; Ddaaki, William; Nakubulwa, Rosette; Nakyanjo, Neema; Nalugoda, Fred; Kagaayi, Joseph; Kigozi, Godfrey; Denison, Julie A; Gaydos, Charlotte; Kennedy, Caitlin E (BMJ Publishing Group Ltd, 2023)
Abstract Introduction Self-collected samples (SCS) for sexually transmitted infection (STI) testing have been shown to be feasible and acceptable in high-resource settings. However, few studies have assessed the acceptability of SCS for STI testing in a general population in low-resource settings. This study explored the acceptability of SCS among adults in south-central Uganda. Methods Nested within the Rakai Community Cohort Study, we conducted semistructured interviews with 36 adults who SCS for STI testing. We analysed the data using an adapted version of the Framework Method. Results Overall, SCS was acceptable to both male and female participants, regardless of whether they reported recent STI symptoms. Perceived advantages of SCS over provider-collection included increased privacy and confidentiality, gentleness and efficiency. Disadvantages included the lack of provider involvement, fear of self-harm and the perception that SCS was unhygienic. Most participants preferred provider-collected samples to SCS. Nevertheless, almost all said they would recommend SCS and would do it again in the future. Conclusion SCS are acceptable among adults in this low-resource setting and could be offered as an additional option to expand STI diagnostic services.
Keywords: sexually transmitted infection (STI); Rakai, Uganda